2022
DOI: 10.3390/ma15238385
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Application of Modified Sn-Based Solder in Cable Intermediate Joints

Abstract: With the increasing use of underground cables, the quantity and quality of intermediate joints demanded are also increasing. The quality of the traditional crimping intermediate joint is easily affected by the actual process of the operator, which may lead to the heating of the crimping part of the wire core, affecting the insulation performance of the cable, and finally causing the joint to break. However, aluminothermic reactive technology has some problems, such as a high welding temperature and an uncontro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Yang et al [7] pointed out that the electric field strength and temperature at the cable joint are higher, making it more prone to thermal stress and electrical stress distortion, thereby affecting the safe operation of the cable joint. Other studies [8,9] also indicate the cable joints are the weak links in cable circuits and are most susceptible to failures.…”
Section: Introductionmentioning
confidence: 97%
“…Yang et al [7] pointed out that the electric field strength and temperature at the cable joint are higher, making it more prone to thermal stress and electrical stress distortion, thereby affecting the safe operation of the cable joint. Other studies [8,9] also indicate the cable joints are the weak links in cable circuits and are most susceptible to failures.…”
Section: Introductionmentioning
confidence: 97%
“…The performance of the cable affects its insulation, finally causing the joint to break. To solve this issue, Xuehua Wu's group successfully changed the content of In in a Sn-1.5Cu-based solder using the brazing principle and microalloying method [15]. The authors found that the maximum conductivity of the solder reached 3.8% and 5%.…”
mentioning
confidence: 99%